Non-Hodgkin's lymphoma as a cause of acute intussusception of the adult - Ribero, Gustavo; Varela, Daniel (Cirugía del Uruguay, 1996)
The authors present a case of enteric invagination secondary to primary intestinal Non-Hodgkin lymphoma. They point out clinical features and analyse different forms of anatomoc!inica/ presentation of intestinal lymphomas and their treatment.